Acrylic acid adhesive, high-temperature-resistant protective film and optical conductive film
By using isocyanate-grafted acrylic polymer and multifunctional group crosslinking monomer cured under UV light, the problems of stability and small molecule transfer in traditional adhesives at high temperatures are solved, and the efficient protection of the optical conductive film and the stability of optical properties are achieved.
Patent Information
- Application Number
- CN202411890277.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
In the prior art, the silicone protective film has silicon transfer problems, which reduces the surface energy of the optical base film; while the acrylic adhesive that has been matured through high temperature requires release film protection, which is uneconomical and may lead to small molecules transfer, affecting optical performance. At the same time, traditional acrylic adhesives require a post-mature process, resulting in the protection film being unable to be stably removed, affecting use.
The crosslinking monomer with isocyanate grafted acrylic polymer and multifunctional group crosslinking monomer are cured by UV under the action of a photoinitiator to improve the crosslinking density and mechanical strength of the acrylic adhesive, achieving rapid curing and high-temperature stability.
The cross-linking density and mechanical strength of acrylic adhesives are improved, the precipitation of small molecules at high temperatures is avoided, the surface energy of the optical conductive film is protected, the stability of optical performance is ensured, and the production cost and complexity of the production process are significantly reduced.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive films, in particular to an acrylic adhesive, a high temperature resistant protective film and an optical conductive film. Background Art
[0002] With the rapid development of electronic products, the market demand for flexible conductive films is growing due to their excellent optical properties, high temperature resistance and good conductivity. In the actual production process of optical conductive films, conductive coatings and strong acid and alkali cleaning are required. In order to protect the conductive film from contamination, a layer of high temperature resistant protective film needs to be attached to the other side. Commonly used high temperature resistant protective films are mainly made of silicone or high temperature cured acrylic adhesives.
[0003] However, the silicone protective film has the problem of silicon transfer, which will reduce the surface energy of the optical base film. The acrylic high-temperature resistant tape that needs to be cured needs to be protected and cured with a release film before it goes off the line. This is not only uneconomical, but the release layer agent of the release film may also be transferred to the surface of the adhesive layer, and finally adhered to the optical base film, resulting in a decrease in the surface energy of the optical base film. In addition, if the acrylic adhesive is directly attached to the optical base film, since traditional acrylic adhesives require a post-curing (high-temperature cross-linking) process (placed at room temperature for more than 7 days or at high temperature for more than 3 days) to completely cross-link with the added cross-linking agent, the lack of curing will cause the final protective film to be unable to be torn off the optical base film, affecting actual use and resulting in the risk of difficulty or unstable unwinding during use.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] One of the purposes of the present invention is to provide an acrylic adhesive, aiming to solve at least one of the above-mentioned technical problems in the prior art.
[0006] A second object of the present invention is to provide a high temperature resistant protective film.
[0007] A third object of the present invention is to provide an optical conductive film.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] The first aspect of the present invention provides an acrylic adhesive, which is mainly obtained by UV curing an isocyanate-grafted acrylic polymer, a multifunctional cross-linking monomer, a photoinitiator and an optional auxiliary agent.
[0010] The isocyanate-grafted acrylic polymer is mainly obtained by grafting an isocyanate monomer with an acrylic polymer.
[0011] The isocyanate monomer is an isocyanate monomer containing a double bond.
[0012] The multifunctional cross-linking monomer includes PGDA, TMPTA, HDDA or PO-NPGDA.
[0013] Furthermore, the added amount of the multifunctional cross-linking monomer is 0.05-5.0% of the mass of the isocyanate-grafted acrylic polymer, preferably 0.2-2.0%.
[0014] Preferably, the added amount of the photoinitiator is 0.1-1.0% of the mass of the isocyanate-grafted acrylic polymer.
[0015] Preferably, during the UV curing, the light intensity is 10 to 200 mW / cm 2 , absorption energy is 100~500mJ / cm 2 .
[0016] Preferably, in the isocyanate-grafted acrylic polymer, the amount of isocyanate monomer added is 1.0 to 10.0% of the mass of the acrylic polymer.
[0017] Preferably, the grafting temperature is 65-80° C., and the grafting reaction time is 1 to 3 hours.
[0018] Further, the photoinitiator includes at least one of benzil dimethyl ether, dialkoxyacetophenone, methyl benzoylformate, 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinebenzylphenyl)butanone and diphenyl (2,4,6-trimethylbenzoyl)phosphine oxide.
[0019] Preferably, the auxiliary agent includes at least one of a UV blocker, an antioxidant and an antistatic agent.
[0020] Furthermore, the double-bond isocyanate monomer includes isocyanate ethyl acrylate and / or isocyanate ethyl methacrylate.
[0021] Preferably, the weight average molecular weight of the acrylic polymer is 600,000 to 2,000,000.
[0022] Preferably, the molecular weight distribution index of the acrylic polymer is 2-4.
[0023] Preferably, the solid content of the acrylic polymer is 15-80%.
[0024] Furthermore, the acrylic polymer is mainly obtained by polymerizing 30-60 parts of soft monomers, 5-40 parts of hard monomers and 1-60 parts of hydroxyl-containing methacrylic acid monomers in a dispersed solvent under the initiation of a thermal initiator, based on weight parts.
[0025] Preferably, the soft monomer includes at least one of isooctyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, isononyl acrylate, tridecyl methacrylate, heptadecyl methacrylate, octadecyl methacrylate, dodecyl methacrylate, isooctyl methacrylate, lauryl acrylate and isodecyl acrylate.
[0026] Preferably, the hard monomer includes at least one of isobornyl acrylate, benzyl methacrylate, cyclohexyl acrylate, 3,3,5-trimethylcycloethyl acrylate and benzyl acrylate.
[0027] Preferably, the hydroxyl-containing methacrylic acid monomer includes at least one of 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, 6-hydroxyhexyl methacrylate and 8-hydroxyoctyl methacrylate.
[0028] Preferably, the acrylic polymer raw material also includes a functional monomer.
[0029] Preferably, the functional monomer comprises acrylamide and / or methacrylamide.
[0030] Preferably, the thermal initiator includes azobisisobutyronitrile (ADIBN), azobisisobutyronitrile (AIBN), dibenzoyl peroxide (BPO).
[0031] Preferably, the dispersion solvent includes at least one of ethyl acetate, butyl acetate, toluene, xylene and butanone.
[0032] Preferably, the polymerization temperature is 40-80°C and the time is 3-24h.
[0033] Furthermore, the curing lamp used in the UV curing includes a metal halide lamp, a high pressure mercury lamp, an electrodeless lamp, a 365nm wavelength fluorescent lamp or a 365nm LED lamp.
[0034] Preferably, the acid value of the acrylic adhesive is less than 1.0 mgKOH / g.
[0035] Preferably, the Tg value of the acrylic adhesive is 0-40°C.
[0036] Preferably, the gel fraction of the acrylic adhesive is 85-99%.
[0037] Preferably, the initial bonding force of the acrylic adhesive is 5 to 50 g / 25 mm.
[0038] Preferably, the adhesive force change of the acrylic adhesive after high temperature is less than 20g.
[0039] The second aspect of the present invention provides a high temperature resistant protective film, comprising a substrate layer and an acrylic adhesive layer attached to one surface of the substrate layer;
[0040] Wherein, the acrylic adhesive layer is formed by coating the acrylic adhesive.
[0041] Furthermore, the material of the substrate layer is PET, PBT, BOPP or polyimide.
[0042] Preferably, the thickness of the substrate layer is 25 to 180 μm.
[0043] Preferably, the shrinkage rate of the substrate layer in both TD and MD directions is ≤1.0% at 150° C. for 30 min.
[0044] Furthermore, the acrylic adhesive layer has a thickness of 5 to 50 μm, preferably 8 to 18 μm.
[0045] A third aspect of the present invention provides an optical conductive film, comprising a base layer, and a conductive layer and a hardening layer arranged on both sides of the base layer;
[0046] The surface of the hardened layer is adhered with the high temperature resistant protective film;
[0047] Wherein, the acrylic adhesive layer in the high temperature resistant protective film is bonded to the hardening layer.
[0048] Compared with the prior art, the present invention has at least the following beneficial effects:
[0049] The acrylic adhesive provided by the present invention, the isocyanate-grafted acrylic polymer and the multifunctional cross-linking monomer, under the action of a photoinitiator, are UV-cured to improve the cross-linking density and mechanical strength of the acrylic adhesive, so that it can still maintain stable performance at high temperatures. At the same time, the UV curing process is rapid and can be completely cross-linked without the need for additional aging time. This fast curing feature not only improves production efficiency, but also avoids the precipitation of small molecules at high temperatures, thereby protecting the surface energy of the optical conductive film and ensuring the stability of the optical properties. In addition, due to the excellent high temperature resistance and fast curing characteristics of the adhesive, the traditional release material and aging steps are eliminated, thereby significantly reducing production costs and simplifying the production process.
[0050] The high temperature resistant protective film provided by the present invention, in view of the advantages of the above-mentioned acrylic adhesive, can be widely used in application scenarios requiring rapid curing and high-performance bonding, such as assembly of electronic products, fixation of optical components, etc., and has broad application prospects and market potential.
[0051] The optical conductive film provided by the present invention uses a high temperature resistant protective film in the preparation process of the optical conductive film, which can effectively protect the surface of the optical conductive film from scratches and contamination, especially in the steps of plating conductive coating and strong acid and strong alkali cleaning. This protective film matches the thermal shrinkage rate of the optical conductive film substrate, ensuring the flatness in the process, and its excellent heat resistance avoids the problem of difficulty in separating or tearing off the protective film under high temperature environment. The high temperature resistant protective film can also reduce surface energy attenuation, ensure printing performance, avoid atomization, and has anti-coupling effect, which is convenient for winding. In addition, it has extremely low small molecule precipitation at high temperature, will not affect the surface energy of the optical base film, and maintains the stability of optical properties. The use of high temperature resistant protective film eliminates the need for release materials and aging time, thereby significantly reducing production costs and improving process yield and product performance. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0053] Hereinafter, the terms "including", "having" and their cognates, which may be used in various embodiments of the present invention, are intended only to indicate specific features, numbers, steps, operations, elements, components or combinations of the foregoing items, and should not be understood as first excluding the existence of one or more other features, numbers, steps, operations, elements, components or combinations of the foregoing items or adding the possibility of one or more features, numbers, steps, operations, elements, components or combinations of the foregoing items.
[0054] The first aspect of the present invention provides an acrylic adhesive, which is mainly obtained by UV curing an isocyanate-grafted acrylic polymer, a multifunctional cross-linking monomer, a photoinitiator and an optional auxiliary agent.
[0055] The isocyanate-grafted acrylic polymer is mainly obtained by grafting an isocyanate monomer with an acrylic polymer.
[0056] The isocyanate monomer is an isocyanate monomer containing a double bond.
[0057] The multifunctional cross-linking monomer includes PGDA, TMPTA, HDDA or PO-NPGDA.
[0058] The acrylic adhesive provided by the present invention, the isocyanate-grafted acrylic polymer and the multifunctional cross-linking monomer, under the action of a photoinitiator, are UV-cured to improve the cross-linking density and mechanical strength of the acrylic adhesive, so that it can still maintain stable performance at high temperatures. At the same time, the UV curing process is rapid and can be completely cross-linked without the need for additional aging time. This fast curing feature not only improves production efficiency, but also avoids the precipitation of small molecules at high temperatures, thereby protecting the surface energy of the optical conductive film and ensuring the stability of the optical properties. In addition, due to the excellent high temperature resistance and fast curing characteristics of the adhesive, the traditional release material and aging steps are eliminated, thereby significantly reducing production costs and simplifying the production process.
[0059] TPGDA is tripropylene glycol diacrylate; HDDA is hexanediol diacrylate; PO-NPGDA is propoxylated (2) neopentyl glycol diacrylate; and TMPTA is trimethylolpropane triacrylate.
[0060] Furthermore, the added amount of the multifunctional cross-linking monomer is 0.05-5.0% of the mass of the isocyanate-grafted acrylic polymer, preferably 0.2-2.0%.
[0061] Typically, but not limiting, the multifunctional crosslinking monomer may be added in an amount of 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.1%, 5.2%, 5. %, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% or 5.0%, or any value in the range of 0.05% to 5.0%; preferably, the addition amount of the multifunctional cross-linking monomer can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%, or any value in the range of 0.2% to 2.0%.
[0062] Preferably, the added amount of the photoinitiator is 0.1-1.0% of the mass of the isocyanate-grafted acrylic polymer.
[0063] Typically but not limiting, the amount of the photoinitiator added can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1.0% of the mass of the isocyanate-grafted acrylic polymer, or any value within the range of 0.1% to 1.0%.
[0064] Preferably, during the UV curing, the light intensity is 10 to 200 mW / cm 2 , absorption energy is 100~500mJ / cm 2 .
[0065] Typically, but not limiting, the light intensity may be 10 mW / cm 2 , 20mW / cm 2 、30mW / cm 2 , 40mW / cm 2 、50mW / cm 2 、60mW / cm 2 、70mW / cm 2 、80mW / cm 2 、90mW / cm 2 , 100mW / cm 2 、110mW / cm 2 、120mW / cm 2 、130mW / cm 2 、140mW / cm 2 、150mW / cm 2 、160mW / cm 2 、170mW / cm 2 、180mW / cm 2 、190mW / cm 2 or 200mW / cm 2 , or 10mW / cm 2 ~200mW / cm 2 Any value within the range. The absorbed energy can be 100mJ / cm 2 、120mJ / cm 2 、140mJ / cm 2 、160mJ / cm 2 、180mJ / cm 2 、200mJ / cm 2 、220mJ / cm 2 、240mJ / cm 2 、260mJ / cm 2 、280mJ / cm 2 、300mJ / cm 2 、320mJ / cm2 、340mJ / cm 2 、360mJ / cm 2 、380mJ / cm 2 、400mJ / cm 2 、420mJ / cm 2 、440mJ / cm 2 、460mJ / cm 2 or 500mJ / cm 2 , or 100mJ / cm 2 ~500mJ / cm 2 Any value in the range.
[0066] Preferably, in the isocyanate-grafted acrylic polymer, the amount of isocyanate monomer added is 1.0-10.0% of the mass of the acrylic polymer. The isocyanate group (-NCO) on the isocyanate monomer combines with the hydroxyl group (-OH), successfully grafting the isocyanate monomer with a double bond onto the acrylic polymer.
[0067] Typically but not limiting, the amount of isocyanate monomer added can be 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5% or 10.0% of the mass of the acrylic polymer, or any value within the range of 1.0% to 10.0%.
[0068] Preferably, the grafting temperature is 65-80° C., and the grafting reaction time is 1 to 3 hours.
[0069] Typically but not limiting, the grafting reaction time may be 1 h, 1.5 h, 2 h, 2.5 h or 3 h, or any value within the range of 1 h to 3 h.
[0070] Further, the photoinitiator includes at least one of benzil dimethyl ether, dialkoxyacetophenone, methyl benzoylformate, 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinebenzylphenyl)butanone and diphenyl (2,4,6-trimethylbenzoyl)phosphine oxide.
[0071] Preferably, the auxiliary agent includes at least one of a UV blocker, an antioxidant and an antistatic agent.
[0072] Furthermore, the double-bond isocyanate monomer includes isocyanate ethyl acrylate and / or isocyanate ethyl methacrylate.
[0073] Preferably, the weight average molecular weight of the acrylic polymer is 600,000 to 2 million, preferably 1 million to 1.5 million. If the weight average molecular weight of the acrylic polymer is lower than 600,000, the polymer has poor high temperature resistance and is prone to residual adhesive and small molecule residues at high temperatures. If the weight average molecular weight of the acrylic polymer exceeds 2 million, the polymer viscosity is extremely high and cannot be coated, and the pressure-sensitive adhesive itself loses its initial adhesion and cannot be wetted and bonded to the adhered object.
[0074] Typically but not limiting, the weight average molecular weight of the acrylic polymer may be 600,000, 700,000, 800,000, 900,000, 1,000,000, 1,100,000, 1,200,000, 1,300,000, 1,400,000, 1,500,000, 1,600,000, 1,700,000, 1,800,000, 1,900,000 or 2,000,000, or any value within the range of 600,000 to 2,000,000. Preferably, the weight average molecular weight of the acrylic polymer may be 1,000,000, 1,100,000, 1,200,000, 1,300,000, 1,400,000, 1,500,000, or any value within the range of 1,000,000 to 1,500,000.
[0075] Preferably, the molecular weight distribution index of the acrylic polymer is 2 to 4. When the molecular weight distribution index is within this range, the polymer itself can have good cohesion and reduce the risk of residual at high temperature. The molecular weight distribution index is obtained by calculating the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn).
[0076] Typically but not limiting, the molecular weight distribution index of the acrylic polymer may be 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9 or 3.0, or any value within the range of 2.0 to 4.0.
[0077] Preferably, the acid value of the acrylic adhesive is less than 1.0 mgKOH / g, which reduces the risk of acid corrosion of the metal oxide coating when the acrylic adhesive is attached to the film on the surface of the metal oxide coating such as ITO during the process protection.
[0078] Preferably, the Tg value of the acrylic adhesive is 0-40°C.
[0079] Typically but not limitatively, the glass transition temperature (Tg value) of the acrylic adhesive may be 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C or 40°C, or any value within the range of 0°C to 40°C.
[0080] Preferably, the solid content of the acrylic polymer is 15-80%.
[0081] Typically but not limiting, the solid content of the acrylic polymer can be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%, or any value within the range of 15% to 80%.
[0082] Furthermore, the acrylic polymer is mainly obtained by polymerizing 30-60 parts of soft monomers, 5-40 parts of hard monomers and 1-60 parts of hydroxyl-containing methacrylic acid monomers in a dispersed solvent under the initiation of a thermal initiator, based on weight parts.
[0083] Typically but not limiting, the weight percentage of the soft monomer can be 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts or 60 parts, or any value in the range of 30 to 60 parts; the weight percentage of the hard monomer can be 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts or 40 parts, or any value in the range of 5 to 40 parts. The weight percentage of the hydroxyl-containing methacrylic acid monomer can be 1 part, 5 parts, 10 parts, 20 parts, 30 parts, 40 parts, 50 parts or 60 parts, or any value in the range of 1 to 60 parts.
[0084] Preferably, the soft monomer includes at least one of isooctyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, isononyl acrylate, tridecyl methacrylate, heptadecyl methacrylate, octadecyl methacrylate, dodecyl methacrylate, isooctyl methacrylate, lauryl acrylate and isodecyl acrylate.
[0085] Preferably, the hard monomer includes at least one of isobornyl acrylate, benzyl methacrylate, cyclohexyl acrylate, 3,3,5-trimethylcycloethyl acrylate and benzyl acrylate.
[0086] Preferably, the hydroxyl-containing methacrylic acid monomer includes at least one of 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, 6-hydroxyhexyl methacrylate and 8-hydroxyoctyl methacrylate.
[0087] Preferably, the acrylic polymer raw material also includes a functional monomer.
[0088] Preferably, the functional monomer comprises acrylamide and / or methacrylamide.
[0089] Preferably, the thermal initiator includes azobisisobutyronitrile, azobisisobutyronitrile, and dibenzoyl peroxide.
[0090] Preferably, the dispersion solvent includes at least one of ethyl acetate, butyl acetate, toluene, xylene and butanone.
[0091] Preferably, the polymerization temperature is 40-80°C and the time is 3-24h.
[0092] Furthermore, the curing lamp used in the UV curing includes a metal halide lamp, a high pressure mercury lamp, an electrodeless lamp, a 365nm wavelength fluorescent lamp or a 365nm LED lamp.
[0093] Preferably, the gel fraction of the acrylic adhesive is 85-99%.
[0094] Typically but not limiting, the gel fraction of the acrylic adhesive can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% or 99%, or any value within the range of 85% to 99%.
[0095] Preferably, the initial bonding force of the acrylic adhesive is 5 to 50 g / 25 mm.
[0096] Typically but not limitatively, the initial adhesion of the acrylic adhesive can be 5g / 25mm, 10g / 25mm, 15g / 25mm, 20g / 25mm, 25g / 25mm, 30g / 25mm, 35g / 25mm, 40g / 25mm, 45g / 25mm, 50g / 25mm, or any value within the range of 5g / 25mm to 50g / 25mm.
[0097] Preferably, the adhesive force change of the acrylic adhesive after high temperature is less than 20g.
[0098] The initial adhesion of the high temperature resistant protective film (for plain glass, the original surface dyne value reaches 48 dynes or more) is in the range of 5-50g / 25mm. After high temperature treatment, the fluctuation of adhesion is controlled within 20g. Even after high temperature, when the high temperature resistant protective film is peeled off from the plain glass, the dyne value of the plain glass surface remains at 42 dynes or more. Such an adhesion range not only ensures a certain degree of wettability, but also ensures that it can be smoothly torn off from the adhered object after use to avoid residue.
[0099] In addition, the gel fraction of acrylic adhesive is between 85-99%, showing a high degree of crosslinking (network crosslinking). This high degree of crosslinking has two main advantages: on the one hand, it can inhibit the precipitation of small molecules; on the other hand, it ensures the stability of adhesion after high temperature. Therefore, this material can still maintain good bonding performance in high temperature environment.
[0100] The second aspect of the present invention provides a high temperature resistant protective film, comprising a substrate layer and an acrylic adhesive layer attached to one surface of the substrate layer;
[0101] Wherein, the acrylic adhesive layer is formed by coating the acrylic adhesive.
[0102] The high temperature resistant protective film provided by the present invention, in view of the advantages of the above-mentioned acrylic adhesive, can be widely used in application scenarios requiring rapid curing and high-performance bonding, such as assembly of electronic products, fixation of optical components, etc., and has broad application prospects and market potential.
[0103] Furthermore, the material of the substrate layer is PET, PBT, BOPP or polyimide.
[0104] Preferably, the thickness of the substrate layer is 25 to 180 μm.
[0105] Preferably, the shrinkage rate of the substrate layer in both TD and MD directions is ≤1.0% at 150° C. for 30 min.
[0106] The shrinkage in TD and MD directions is comparable to that of the base layer of the optical conductive film. During high temperature, the material will not warp abnormally due to the significant difference in shrinkage between the two. The material selected for the substrate layer has a low additive content, and the material haze changes little after the high temperature process. To prove that the material has low precipitation of small molecules at high temperature, the haze change value after high temperature is limited to <20%. The precipitated small molecules may be transferred to the surface of the glue to pollute the optical material. As a preferred choice, the substrate layer selects the optical PET substrate GM13C of Sichuan Dongcai Technology Group Co., Ltd. as the substrate.
[0107] In some preferred embodiments of the present invention, the material of the substrate layer of the high temperature resistant protective film is the same as the material of the base layer of the optical conductive film.
[0108] Furthermore, the thickness of the acrylic adhesive layer is 5 to 50 μm, preferably 8 to 18 μm. When the thickness is less than 5 μm, the film-forming property is poor, and it is not conducive to blocking the precipitation of small molecules of the base film. When the thickness is higher than 50 μm, the coating efficiency is significantly reduced. It should be noted that the thickness here is the dry adhesive thickness.
[0109] A third aspect of the present invention provides an optical conductive film, comprising a base layer, and a conductive layer and a hardening layer arranged on both sides of the base layer;
[0110] The surface of the hardened layer is adhered with the high temperature resistant protective film;
[0111] Wherein, the acrylic adhesive layer in the high temperature resistant protective film is bonded to the hardening layer.
[0112] The optical conductive film provided by the present invention uses a high temperature resistant protective film in the preparation process of the optical conductive film, which can effectively protect the surface of the optical conductive film from scratches and contamination, especially in the steps of plating conductive coating and strong acid and strong alkali cleaning. This protective film matches the thermal shrinkage rate of the optical conductive film substrate, ensuring the flatness in the process, and its excellent heat resistance avoids the problem of difficulty in separating or tearing off the protective film under high temperature environment. The high temperature resistant protective film can also reduce surface energy attenuation, ensure printing performance, avoid atomization, and has anti-coupling effect, which is convenient for winding. In addition, it has extremely low small molecule precipitation at high temperature, will not affect the surface energy of the optical base film, and maintains the stability of optical properties. The use of high temperature resistant protective film eliminates the need for release materials and aging time, thereby significantly reducing production costs and improving process yield and product performance.
[0113] The present invention is further described below by specific examples and comparative examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form. The raw materials used in the examples and comparative examples of the present invention, if no specific conditions are specified, are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0114] Example 1
[0115] This embodiment provides a high temperature resistant protective film, and the specific preparation method is as follows:
[0116] 1. Add 30 parts of isooctyl acrylate, 40 parts of n-butyl acrylate, 10 parts of isobornyl acrylate, 15 parts of 2-hydroxypropyl acrylate, 5 parts of acrylamide and 40 parts of ethyl acetate into the reactor and mix them evenly. Stir for 20 minutes under nitrogen to remove the air in the reactor. Finally, add thermal initiator BPO, react at 70-80°C for 16 hours, and cool to obtain acrylic polymer.
[0117] 2. Add 1.2 parts of ethyl isocyanate methacrylate to the obtained acrylic polymer, control the reaction temperature to 70° C., and react for 2 hours to obtain an isocyanate-grafted acrylic polymer.
[0118] 3. Add 0.5 parts of 1-hydroxycyclohexyl phenyl ketone and 1 part of HDDA to the isocyanate-grafted acrylic polymer, stir and mix evenly, vacuum degassing, glue on the PET substrate (GM13C, Sichuan Dongcai Technology) with a slit coating head, and bake in a hot cycle box oven until the solvent evaporates completely (dry film thickness 30μm), then heat at 100mW / cm 2 Intensity UVA curing lamp absorbs 300mJ / cm 2 After the energy is applied, it is directly rolled up to obtain a high temperature resistant protective film.
[0119] Example 2
[0120] This embodiment provides a high temperature resistant protective film, and the specific preparation method is as follows:
[0121] 1. Add 30 parts of n-butyl acrylate, 35 parts of dodecyl acrylate, 15 parts of cyclohexyl acrylate, 13 parts of 4-hydroxybutyl acrylate, 6 parts of methacrylamide and 40 parts of butanone into the reactor and mix them evenly. Stir for 20 minutes under nitrogen to remove the air in the reactor. Finally, add thermal initiator azobisisoheptanenitrile, react at 55-65°C for 18 hours, and cool to obtain acrylic polymer.
[0122] 2. Add 2 parts of ethyl isocyanate methacrylate to the obtained acrylic polymer, control the reaction temperature to 75° C., and react for 2 hours to obtain an isocyanate-grafted acrylic polymer.
[0123] 3. Add 0.5 parts of diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide and 0.8 parts of HDDA to the isocyanate-grafted acrylic polymer, stir and mix evenly, vacuum degassing, glue on the PET substrate (GM13C, Sichuan Dongcai Technology) with a slit coating head, bake in a hot cycle box oven until the solvent evaporates completely (dry film thickness 30μm), and then heat at 100mW / cm 2 Intensity UVA curing lamp absorbs 300mJ / cm 2 After the energy is applied, it is directly rolled up to obtain a high temperature resistant protective film.
[0124] Example 3
[0125] This embodiment provides a high temperature resistant protective film, and the specific preparation method is as follows:
[0126] 1. Add 50 parts of n-butyl acrylate, 20 parts of isobornyl acrylate, 28 parts of 2-hydroxypropyl acrylate, 2 parts of methacrylamide and 40 parts of butanone into the reactor and mix them evenly. Stir for 20 minutes under nitrogen to remove the air in the reactor. Finally, add azobisisobutyronitrile as a thermal initiator, react at 70-80°C for 8 hours, and cool to obtain an acrylic polymer.
[0127] 2. Add 5 parts of ethyl isocyanate methacrylate to the obtained acrylic polymer, control the reaction temperature to 75° C., and react for 2 hours to obtain an isocyanate-grafted acrylic polymer.
[0128] 3. Add 0.6 parts of 1-hydroxycyclohexyl phenyl ketone and 0.9 parts of TMPTA to the isocyanate-grafted acrylic polymer, stir and mix evenly, vacuum degassing, glue on the PET substrate (GM13C, Sichuan Dongcai Technology) with a slit coating head, and bake in a hot cycle box oven until the solvent evaporates completely (dry film thickness 30μm), then heat under 100mW / cm2 Intensity UVA curing lamp absorbs 300mJ / cm 2 After the energy is applied, it is directly rolled up to obtain a high temperature resistant protective film.
[0129] Example 4
[0130] This embodiment provides a high temperature resistant protective film, and the specific preparation method is as follows:
[0131] 1. Add 40 parts of n-butyl acrylate, 30 parts of lauryl acrylate, 25 parts of cyclohexyl acrylate, 6 parts of methacrylamide and 100 parts of ethyl acetate into the reactor and mix them evenly. Stir for 20 minutes under nitrogen to remove the air in the reactor. Finally, add azobisisobutyronitrile as a thermal initiator, react at 55-70°C for 8 hours, and cool to obtain an acrylic polymer.
[0132] 2. Add 6 parts of ethyl isocyanate methacrylate to the obtained acrylic polymer, control the reaction temperature to 72° C., and react for 2 hours to obtain an isocyanate-grafted acrylic polymer.
[0133] 3. Add 0.5 parts of diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide and 1 part of HDDA to the isocyanate-grafted acrylic polymer, stir and mix evenly, vacuum degassing, glue on the PET substrate (GM13C, Sichuan Dongcai Technology) with a slit coating head, bake in a hot cycle box oven until the solvent evaporates completely (dry film thickness 30μm), and then heat at 100mW / cm 2 Intensity UVA curing lamp absorbs 300mJ / cm 2 After the energy is applied, it is directly rolled up to obtain a high temperature resistant protective film.
[0134] Example 5
[0135] This embodiment provides a high temperature resistant protective film, and the specific preparation method is as follows:
[0136] 1. Add 40 parts of n-butyl acrylate, 30 parts of lauryl acrylate, 25 parts of cyclohexyl acrylate, 6 parts of methacrylamide and 100 parts of ethyl acetate into the reactor and mix them evenly. Stir for 20 minutes under nitrogen to remove the air in the reactor. Finally, add thermal initiator BPO, react at 80°C for 22 hours, and cool to obtain acrylic polymer.
[0137] 2. Add 10 parts of ethyl isocyanate methacrylate to the obtained acrylic polymer, control the reaction temperature to 73° C., and react for 2 hours to obtain an isocyanate-grafted acrylic polymer.
[0138] 3. Add 0.5 parts of 1-hydroxycyclohexyl phenyl ketone and 0.6 parts of TMPTA to the isocyanate-grafted acrylic polymer, stir and mix evenly, vacuum degassing, glue on the PET substrate (GM13C, Sichuan Dongcai Technology) with a slit coating head, and bake in a hot cycle box oven until the solvent evaporates completely (dry film thickness 30μm), then heat at 100mW / cm 2 Intensity UVA curing lamp absorbs 300mJ / cm 2 After the energy is applied, it is directly rolled up to obtain a high temperature resistant protective film.
[0139] Example 6
[0140] This embodiment provides a high temperature resistant protective film. The difference from Embodiment 3 is that the amount of isocyanate ethyl methacrylate is 7 parts, and the other raw materials and preparation steps are the same as those in Embodiment 3, which will not be repeated here.
[0141] Example 7
[0142] This embodiment provides a high temperature resistant protective film. The difference from Embodiment 1 is that the amount of n-butyl acrylate used is 30 parts, and the other raw materials and preparation steps are the same as those in Embodiment 1, which will not be repeated here.
[0143] Example 8
[0144] This embodiment provides a high temperature resistant protective film. The difference from Embodiment 2 is that the amount of methacrylamide used is 4 parts, the amount of HDDA used is 0.4 parts, and the remaining raw materials and preparation steps are the same as those in Embodiment 2, which will not be repeated here.
[0145] Example 9
[0146] This embodiment provides a high temperature resistant protective film. The difference from Example 3 is that the amount of n-butyl acrylate is 70 parts, the amount of isobornyl acrylate is 15 parts, the amount of 2-hydroxypropyl acrylate is 15 parts, and methacrylamide is not used. The remaining raw materials and preparation steps are the same as those in Example 3 and will not be repeated here.
[0147] Example 10
[0148] This embodiment provides a high temperature resistant protective film, and the specific preparation method is as follows:
[0149] 1. Add 35 parts of n-butyl acrylate, 38 parts of dodecyl acrylate, 20 parts of cyclohexyl acrylate, 6 parts of methacrylamide and 40 parts of butanone into the reactor and mix them evenly. Stir for 20 minutes under nitrogen to remove the air in the reactor. Finally, add thermal initiator azobisisoheptanenitrile, react at 55-60°C for 12 hours, and cool to obtain acrylic polymer.
[0150] 2. Same as the step in Example 2.
[0151] 3. Same as the step in Example 2.
[0152] Comparative Example 1
[0153] This comparative example provides a high temperature resistant protective film. The difference from Example 2 is that step 2 is omitted, and acrylic polymer is directly used to prepare acrylic adhesive. The remaining raw materials and steps are the same as those in Example 2 and will not be repeated here.
[0154] Comparative Example 2
[0155] This comparative example provides a high temperature resistant protective film. The difference from Example 2 is that hexamethylene diisocyanate trimer is used to replace HDDA. The remaining raw materials and steps are the same as those in Example 2 and will not be repeated here.
[0156] Test Example 1
[0157] The acrylic acid polymer obtained in step 1 of the examples and comparative examples was tested.
[0158] Polymer concentration test: Take the liquid glue obtained after polymerization, weigh M1 (usually 0.2-1.0g), put it into an iron box (the weight of the iron box is recorded as M2), put it at 150℃ to dry for more than 30 minutes, and then weigh the total weight of the dry glue and the iron box, recorded as M3.
[0159] Polymer concentration = (M3-M2) / M1*100. The calculated data are recorded in Table 1.
[0160] Molecular weight (Mw) and molecular weight distribution (Mw / Mn): The molecular weight of the polymer was evaluated using gel permeation chromatography (GPC). The polymer was dissolved in tetrahydrofuran at a concentration of 0.5 (weight / volume)% and passed through a 0.2 micron polytetrafluoroethylene filter. A sample of the resulting solution was analyzed using a Waters Corp., Milford, MA, USA GPC unit equipped with two PLgel 5 micron MIXED-D columns (Styragel HR5E 7.8 mm×300 mm) at 35°C (available from Waters Corp., Milford, MA, USA) and UV (model 2487) and refractive index (model 2410) detectors. After injection, the sample was eluted at 1 ml / min. Calibration was performed using polystyrene standards. Mw and Mn were determined and reported in kilodaltons (kDa). The results are recorded in Table 1.
[0161] Table 1
[0162]
[0163] Test Example 2
[0164] The high temperature resistant protective films obtained in the examples and comparative examples were subjected to the following tests.
[0165] Gel fraction
[0166] The degree of crosslinking was gravimetrically analyzed by weighing a sample of the cured film, soaking it in ethyl acetate solvent for 24 hours, filtering it through a 200 mesh filter, and then drying it under vacuum at 150°C for at least 30 minutes. Two samples were run and the average was reported, and the percentage was calculated using the following formula:
[0167] Gel fraction % = 100 (AB) / C
[0168] A is the weight of the filter and dry glue after drying; B is the weight of the filter; C is the weight of the original glue (before soaking).
[0169] Initial adhesion
[0170] The high temperature resistant protective film was cut into sample strips of 25mm*15cm, attached to the glass substrate, rolled back and forth 3 times with a 2kg roller at a speed of 300mm / min, and placed under constant temperature and humidity conditions (22±3℃, 60±5%RH) for 30min. The adhesion of the adhesive layer to the glass plate was tested using a tensile testing machine at a speed of 300mm / min.
[0171] High temperature initial adhesion
[0172] The high temperature resistant protective film was cut into 25mm*15cm sample strips, attached to the glass substrate, rolled back and forth 3 times with a 2kg roller at a speed of 300mm / min, and placed under constant temperature and humidity conditions (160℃*2h) for 30min. The adhesion of the adhesive layer to the glass plate was tested using a tensile testing machine at a speed of 300mm / min.
[0173] Glass transition temperature of adhesive layer (Tg)
[0174] The rheological dynamic analyzer (model DHR-2 rheometer, TA Instruments, NewCastle, DE, USA) was used for determination in parallel plate mode. The film was pressed to a thickness of about 1 mm (0.039 inches). The sample was punched out using a circular mold with a diameter of 8 mm (0.315 inches), and after removing the release liner, it was centered between two parallel plates each with a diameter of 8 mm. The plate with the adhesive was positioned in the rheometer and compressed until the edge of the adhesive film was consistent with the edge of the top plate and the bottom plate. The temperature was increased from -30°C to 120°C at 5°C / min, while the parallel plates oscillated at an angular frequency of 1 radian / second and a constant strain of 10%. The relationship curves between temperature and storage modulus (G'), loss modulus (G") and loss factor were obtained, and the temperature corresponding to the maximum loss factor in the range of -10°C-50°C was recorded as Tg.
[0175] ITO film corrosion (ITO resistance change rate)
[0176] Cut the high temperature resistant protective film into 50mm*50mm, attach it to the conductive surface of the ITO film, apply 0.2-0.5g of high temperature and high humidity silver conductive glue at 5mm from the upper and lower edges of the protective film, and after the conductive glue is completely cured at high temperature, use a multimeter to record the resistance value T1, then put the combination into a 60℃, 90%RH environment for 240h, take it out, cool it at room temperature, and then use a multimeter to record the resistance value T2, the resistance change rate = (T2-T1) / T1*100%. If the resistance change rate is ≤10%, it is considered as qualified for corrosion.
[0177] Dyne value of plain glass surface
[0178] When using the German "ARCOTEC" dyne pen for testing, an intermediate value should be selected as the starting point. For example, when testing with a 38mN / m dyne pen, if the test pen wets the surface of the glass within 2 seconds, the surface tension of the glass is greater than or exactly the selected value. In this case, a test pen with a larger value needs to be selected for the second test, and so on, until the test result shrinks into a water drop shape (small water balls that are evenly distributed in the scratches) within 2 seconds. In this case, the value before this test is regarded as the surface value of the substrate.
[0179] If the water shrinks into a droplet shape in the scratch on the plain glass during the first test, use a test pen with a smaller value to perform a second test until the surface of the plain glass is wet (the scratched mark remains unchanged after a few seconds). The value of this test is regarded as the surface value of the plain glass.
[0180] The data obtained from the above test are shown in Table 2 below.
[0181] Table 2
[0182]
[0183] As can be seen from Table 2, by introducing the grafted monomer and then photocrosslinking through the multifunctional crosslinking monomer, rapid curing and crosslinking can be achieved, the protective film can be directly rolled up, and there will be no residual glue on the back of the protective film when unrolling, and the high temperature resistance and small molecule transfer are significantly better than the finished product of the heating curing crosslinker.
[0184] Finally, it should be noted that the above-described embodiments are only specific implementations of the present invention, which are used to illustrate the technical solutions of the present invention, rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention is described in detail with reference to the above-described embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the above-described embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. An acrylic adhesive, characterized in that: It is mainly obtained by UV curing of isocyanate-grafted acrylic polymer, multifunctional cross-linking monomer, photoinitiator and optional auxiliary agent; The isocyanate-grafted acrylic polymer is mainly obtained by grafting an isocyanate monomer with an acrylic polymer; The isocyanate monomer is an isocyanate monomer containing a double bond; The multifunctional cross-linking monomer includes PGDA, TMPTA, HDDA or PO-NPGDA.
2. The acrylic adhesive according to claim 1, characterized in that: The amount of the multifunctional cross-linking monomer added is 0.05 to 5.0% of the mass of the isocyanate-grafted acrylic polymer, preferably 0.2 to 2.0%; Preferably, the amount of the photoinitiator added is 0.1 to 1.0% of the mass of the isocyanate-grafted acrylic polymer; Preferably, during the UV curing, the light intensity is 10 to 200 mW / cm 2 , absorption energy is 100~500mJ / cm 2 ; Preferably, in the isocyanate-grafted acrylic polymer, the amount of isocyanate monomer added is 1.0 to 10.0% of the mass of the acrylic polymer; Preferably, the grafting temperature is 65-80° C., and the grafting reaction time is 1 to 3 hours.
3. The acrylic adhesive according to claim 1, characterized in that: The photoinitiator comprises at least one of benzil dimethyl ether, dialkoxy acetophenone, methyl benzoylformate, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinebenzylphenyl)butanone and diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide; Preferably, the auxiliary agent includes at least one of a UV blocker, an antioxidant and an antistatic agent.
4. The acrylic adhesive according to any one of claims 1 to 3, characterized in that: The double-bond isocyanate monomers include isocyanate ethyl acrylate and / or isocyanate ethyl methacrylate; Preferably, the weight average molecular weight of the acrylic polymer is 600,000 to 2,000,000; Preferably, the molecular weight distribution index of the acrylic acid polymer is 2 to 4; Preferably, the solid content of the acrylic polymer is 15-80%.
5. The acrylic adhesive according to any one of claims 1 to 3, characterized in that: The acrylic polymer is mainly obtained by polymerizing 30 to 60 parts of soft monomers, 5 to 40 parts of hard monomers and 1 to 60 parts of hydroxyl-containing methacrylic acid monomers in a dispersed solvent under the initiation of a thermal initiator. Preferably, the soft monomer includes at least one of isooctyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, isononyl acrylate, tridecyl methacrylate, heptadecyl methacrylate, octadecyl methacrylate, dodecyl methacrylate, isooctadecyl methacrylate, lauryl acrylate and isodecyl acrylate; Preferably, the hard monomer includes at least one of isobornyl acrylate, benzyl methacrylate, cyclohexyl acrylate, 3,3,5-trimethylcycloethyl acrylate and benzyl acrylate; Preferably, the hydroxyl-containing methacrylic acid monomer includes at least one of 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, 6-hydroxyhexyl methacrylate and 8-hydroxyoctyl methacrylate; Preferably, the acrylic polymer raw material further includes a functional monomer; Preferably, the functional monomer comprises acrylamide and / or methacrylamide; Preferably, the thermal initiator includes azobisisobutyronitrile, azobisisobutyronitrile, dibenzoyl peroxide; Preferably, the dispersion solvent comprises at least one of ethyl acetate, butyl acetate, toluene, xylene and butanone; Preferably, the polymerization temperature is 40-80°C and the time is 3-24h.
6. The acrylic adhesive according to any one of claims 1 to 3, characterized in that: The curing lamp used in the UV curing includes a metal halide lamp, a high pressure mercury lamp, an electrodeless lamp, a 365nm wavelength fluorescent lamp or a 365nm LED lamp; Preferably, the acid value of the acrylic adhesive is less than 1.0 mgKOH / g; Preferably, the Tg value of the acrylic adhesive is 0 to 40°C; Preferably, the gel fraction of the acrylic adhesive is 85-99%; Preferably, the initial bonding force of the acrylic adhesive is 5 to 50 g / 25 mm; Preferably, the adhesive force change of the acrylic adhesive after high temperature is less than 20g.
7. A high temperature resistant protective film, characterized in that: It includes a substrate layer and an acrylic adhesive layer attached to one side surface of the substrate layer; Wherein, the acrylic adhesive layer is formed by coating the acrylic adhesive according to any one of claims 1 to 6.
8. The high temperature resistant protective film according to claim 7, characterized in that: The material of the substrate layer is PET, PBT, BOPP or polyimide; Preferably, the thickness of the substrate layer is 25 to 180 μm; Preferably, the shrinkage rate of the substrate layer in both TD and MD directions is ≤1.0% at 150° C. for 30 min.
9. The high temperature resistant protective film according to claim 7, characterized in that: The thickness of the acrylic adhesive layer is 5 to 50 μm, preferably 8 to 18 μm.
10. An optical conductive film, characterized in that: It includes a base layer and a conductive layer and a hardening layer arranged on both sides of the base layer; The surface of the hardened layer is adhered with the high temperature resistant protective film according to any one of claims 7 to 9; Wherein, the acrylic adhesive layer in the high temperature resistant protective film is bonded to the hardening layer.